Oscillations in Spontaneous and Visually Evoked Neuronal Activity in the Superficial Layers of the Cat's Superior Colliculus - Foik, Andrzej T.; Ghazaryan, Anaida; Waleszczyk, Wioletta J. (Frontiers in Systems Neuroscience, 2018)
Oscillations are ubiquitous features of neuronal activity in sensory systems and are considered as a substrate for integration of sensory information. Several studies have described oscillatory activity in the geniculate visual pathway, but little is known about this phenomenon in the extrageniculate visual pathway. We describe oscillations in evoked and background activity in the cat's superficial layers of the superior colliculus (sSC), a retinorecipient structure in the extrageniculate visual pathway. Extracellular single-unit activity was recorded during periods with and without visual stimulation. Autocorrelation, FFT and renewal density analyses were used to detect and characterize oscillations in the neuronal activity. Oscillations were common in background and stimulus evoked activity. Oscillations were observed in about half of the cells and could appear in two forms – stimulus phase-locked, and stimulus phase-independent oscillations. Stimulus phase-independent and background oscillatory frequencies were very similar suggesting that stimulus phase-independent oscillations may be a form of enhanced “spontaneous” oscillations. Stimulus phase-locked oscillations were present in responses to moving and flashing stimuli. In contrast to stimulus phase-independent oscillations, the strength of phase-locked oscillations was positively correlated with stimulus velocity and neuronal firing rate. Our results suggest that sSC phase-independent oscillations may be generated by the same mechanism(s) that lie in the base of “spontaneous” oscillations, while phase-locked oscillations may result from interactions within the intra-collicular network and/or from a phase reset of oscillations present in the background activity.